Composition Determination from Strain Relaxation in 4D-STEM - F. Otto; L. Niermann; T. Niermann; M. Lehmann (Applied Physics Express, 2025)
Composition determination with high spatial resolution is crucial for device engineering of electronic and optoelectronic systems. While scanning transmission electron microscopy (STEM) can infer material composition from strain with high precision, multiple scattering effects (dynamic diffraction) often hinder accurate evaluation. This challenge is amplified by the inevitable relaxation of strain at the surfaces of thin TEM lamellae, leading to variations in dynamic diffraction patterns. Here, we introduce a method that directly exploits these variations from surface relaxation to extract composition, lamella thickness, and width of a quantum well within a known substrate, all from a single 4D-STEM measurement.